In-situ ultrasonic methods for monitoring the hydrothermal synthesis of LTA-type zeolite from colloidal solutions - Baser, Hasan-Hüseyin; Thangaraj, Thangaraj; Herrmann, Ralph; Ofili, Ifeanyi Jimmy; Schwieger, Wilhelm (Studies in Surface Science and Catalysis, 2007)
In the present study, we report the successful use of ultrasound device as a real-time, in situ diagnostic tool for monitoring the crystallization progress of zeolite A from homogeneous colloidal solutions with the composition 0.4 Na(2)O : 10 SiO(2) : 1.4 Al(2)O(3) : 16 (TMA)(2)O: 650 H(2)O. The results demonstrate that there exist good correlation between the crystallisation progress of zeolite A in terms of yield and the attenuated ultrasonic signal. It is also revealed that the kinetic information like activation energy of crystallisation reaction could be easily calculated from the measured ultrasonic signals data. In the studied case, activation energy of Ca. 30 kJ/mol was obtained.